Perancangan Sistem Komunikasi Data pada Pelayanan Bus Malam Menggunakan Barcode dan GPS Shield Berbasis Web dan Raspberry Pi - Adi Putra Wijaya (Jurnal Jaringan Telekomunikasi, 2017)
The bus is one of the mass transportation used by many people. With the rapid development of technology to find out the position of the bus, you can use a GPS tracker which has the ability to transmit real-time data. Use the barcode added to the bus ticket to find out the status of passengers getting on or off. Raspberry Pi functions to control Modem, Barcode Scanner, GPS Tracker. Raspberry Pi will process the GPS Tracker data on the bus to find out the coordinates of the bus. Barcode and GPS Tracker information will be retrieved from the webserver. Users will get bus information via a web smartphone by sending the bus police ID number. The application features contain agent information, bus destination code information, bus departure hours, bus tracking, and passenger status. Based on the test results, the tolerance value is 0.1" for latitude, the distance meter longitude value is 0.2". GPS Tracker will send more accurate data when in the city. In the Malang-Jakarta GPS Tracker test, there were not too many tree obstacles. Barcodes that have been scanned using a barcode reader will turn the seats on the display green.